Essential nutrient element profiles in rice types: a risk–benefit assessment including inorganic arsenic. Issue 5 (14th September 2022) - Menon, Manoj; Smith, Amelia; Fennell, Joseph
Abstract: Rice is consumed by nearly half of the global population and a significant source of energy and nutrients. However, rice consumption can also be a significant pathway of inorganic arsenic (iAs) exposure, thus requiring a risk–benefit assessment. This study assessed nutrient element (NE) densities in fifty-five rice types (white, brown and wild rice) marketed in the UK. Densities of essential NE were used to rank rice types in meeting daily NE targets under different consumption scenarios through a newly developed optimisation approach. Using iAs data from these rice types, we assessed the margin of exposure (MOE) for low (the UK) and high (Bangladesh) rice intake scenarios. Our results showed that brown and wild rice are significantly higher in many NE and significantly contribute to dietary reference value (DRV). Our modelling showed that switching to brown or wild rice could increase the intake of several essential nutrients by up to eight times that of white rice. Using rice consumption data for mid-to-high-consumption countries, we estimate that brown rice could provide 100 % adult DRV for Fe, Mg, Cr, P and Mo, and substantial contributions for Zn, Se and K. Our results show that the amount of rice primarily determines risk from iAs consumed rather than the type of rice. Therefore, switching from white to brown or wild rice could be beneficial, provided iAs concentration in rice is within the recommended limits.